Audit committee expertise and financial reporting quality: an empirical study in Malaysia - Puat Nelson, Sherliza (Lambert Academic Publishing, 2011)
Since Sarbanes Oxley Act 2002, there has been growing interest in the research concerning audit committee expertise. Audit committee plays an important role on the quality and credibility of financial reporting, since they effectively function as a governance mechanism. Whilst, many studies have examined the attributes of audit committee financial expertise with regard to financial reporting quality, and their composition of expertise on the audit committee board, few have focused on the financial expertise aspect specifically and none have considered extending the meaning of expert other than the notion of a professionally qualified accountant. This study examines the audit committee expertise attribute in detail and investigates the relationship between these expertise attributes and financial reporting quality, and thus, complements extant literature on audit committee expertise